The Influence of Financial Literacy and Lifestyle on the Academic Achievement of Almarisah Madani University Students - Rano, Jessie Alisa; Hasrina, Sri; Yusril, Basso; Patanduk, Theby Kharisma; Patulak, Britney Iveny (Jurnal Ekonomi, 2024)
The influence of literacy and lifestyle on students is an interesting subject in the study of campus life. Literacy, covering financial, media, and information literacy, provides a strong foundation for students to develop a deep understanding of the ever-evolving world. Meanwhile, lifestyle reflects students' daily behavioral patterns, from shopping habits to social media preferences. Students with good financial literacy tend to be better able to manage their finances wisely, including spending on academic needs such as books and tuition fees. A balanced combination of financial literacy and lifestyle can form students who are more aware of information, in decision making, and better able to navigate challenges and opportunities in the future. This study aims to investigate the influence of literacy and lifestyle on students of Almarisah Madani University. The method in this study uses a survey approach to collect data from a sample of students. The research instrument is a questionnaire that includes statements related to literacy and lifestyle. Data were analyzed using descriptive statistical techniques and multiple linear regression to identify relationships between variables. The number of samples used in this study was 372 students with the sampling technique being Stratified Cluster Proportional Random Sampling. The results of this study are expected to provide a better understanding of the importance of literacy and lifestyle for students in the context of Almarisah Madani University.